Wealth and Consumption in Australia. (26th February 2020) - May, Diego; Nodari, Gabriela; Rees, Daniel M.
Abstract: We revisit the evidence on the effect of changes in household wealth on consumption using a panel of Australian states. We find that a one per cent increase in the value of housing wealth increases consumption by about 0.16 per cent in the long‐run, with half of the response occurring within two quarters. The size of this response has been stable over time and largely reflects changes in spending on motor vehicles, durable goods and other discretionary items. We then run counterfactual scenarios using the Reserve Bank of Australia's macroeconometric model, MARTIN, to assess the macroeconomic effects of changes in household wealth. We show that increases in household wealth supported household spending between 2013 and 2017, when growth in disposable income was weak.